Efeito de flavonóides na germinação e no crescimento assimbiótico de fungos micorrízicos vesiculo-arbusculares - Baptista, Mírian Josefina (1993)
Vesicular arbuscular mycorrhizal symbiosis (VAM) are of great ecological and agricultural importance, because of their nutritional benefits and improved plant productivity. However, the use of these fungi in agriculture is stil wery limited since they can not be grown in purê culture, and inoculum production is very dificult. It has been recently demonstrated that plant phenolic compounds act as signal molecules for the development of several symbiosis between plant roots and microorganisms. In the case of mycorrhizae, the involviment of such compounds is stil under investigation. However, some plant flavonoids has been shown to be active against vesicular-arbuscular mycorrhizal fungi. In this study, we examined the effects of several synthetic flavonoid compounds on VAM fungal spore germination and assymbiotic mycelial growth in defined media. For germination experiments, surface sterilized spores were incubated in water agar 1%. suplemented with flavonoids to be tested. Spore germination was assessed after 2, 5 and 10 days of incubation. For the mycelial growth experiments, pre- germinated spores were transfered to glass tubes containing liquid nutrient media suplemented with various flavonóides at concentration ranging from 1 to 50 uM . Mycelial growth was assessed after 15 days of incubation by a hyphal intersection method. The flavonóis morin, quercetin, fisetin; the isoflavonoid biochanin A; a flavone and the flavanones naringeriin, hesperetin and taxi foi in exhibited inhibitory effects on spore germination. The inhibitory activity varied with their chemical structure, concentration and incubation period. After 2 days of incubation the inhibitory effect was greater than at 5 or 10 days. Rercent inhibition on germination at 2 days, rangedfrom 16% ( quercetin 60 uM ) to over 80% for taxi foiinat 200 uM and flavone at 100 uM. Other flavonoids such as formononetin, apigenin and genistein showed no inhibitory effects on spore germination. Most compounds tested showed inhibition for mycelia growth. Only the flavones apigenin and flavone; the isoflavonoids genistein and daidzein and the flavanone taxifolin showed no significant effects on hyphal growth . The isoflavone biochanin A showed linear inhibitory effects, whereas, the flavonóis quercetin, myricetin, morin, kaempferol and fisetin; the flavanones hesperetin and naringenin; and the isoflavonoid formononetin estimulated the mycelial growth. Flavonoid activity was related to concentration and chemical structure. The presence of several -0H groups on the B ring of the flavonóis and the insaturation on the C2-C3 position of the flavanones are commum features of stimulatory activity of these compounds. The presence of methylation at the 4 position with a hidroxil group at the 5 position were related to inhibitory activity of the isoflavonoids. The absence of hidroxil group at the 5 position was related to stimulatory activity of these class of flavonoids. The results obtained in the present study,suqgest that flavonoids exhibit significative effects on both germination and mycelial growth of VAM fungi "in vitro". Such effects can be either stimulatory or inhibitory depending on concetration and type of compound. This idicates the potential role of flavonoids as regulatory signals for fungai development and for VAM establishment.